GVCS and centrality Mapping key hubs, spokes and the periphery - Criscuolo, Chiara (OECD Publishing, 2018)
This paper uses "centrality" metrics to reflect position with Global Value Chains (GVCs). Central sectors reflect those that are highly connected (both directly and indirectly) and influential within globalproduction networks, whereas peripheral sectors exhibit weak linkages and are less influential. Applying these metrics to OECD ICIO data, reveals there have been profound changes in the structure of GVCs over the period 1995-2011. Whilst some activities remain clustered around the same key hubs as was the case at the start of the period (e.g. motor vehicles), for others there have been dramatic changes in the geography of economic activity (e.g. IT manufacturing), whereas other activities have become more influential for value chains almost universally (e.g. IT services). Several emerging economies and their industries have become more central to global production networks. We find this is particularly true of most peripheral industries of Eastern European countries, with their growing importance coinciding with the timing of their EU accession. Asian value chains have also undergone substantial reorganisation. In particular, the centrality of Japanese industries has fallen from an initial position of being the key hub within Asian value chains and the bulk of this fall does not appear to be due to the decline in size of the Japanese economy over this period. This is in contrast with trends in foreign value added content of exports of these Japanese industries, which increased over the same time period, illustrating that the centrality measure does not seem to simply reflect features captured by existing GVC metrics
Keywords: Science and Technology; Economics